Urban Organic Farming: Farming Business Analysis of Vigur O Women's Farmer Group, Malang City - Sri Muljaningsih (Journal of International Conference Proceedings (JICP), 2022)
In general, urban land is not intended for agriculture, but some people live in suburban settlements, taking the initiative to become farmers due to the community's need for healthy food from organic farming, such as vegetables. The problem of organic vegetables is not available in Traditional Markets but Modern Markets with quite expensive prices. Therefore, it is possible to become an organic vegetable farmer in urban areas, assuming transport cost efficiency, because it is close to the market. Therefore, the Vigur O Women Farmers Group (KWT) is a community that participates in the 2010 Go Organic government program and has received a certificate (SNI) Organic from LeSOS, so this study has a purpose, to analyze organic vegetable farming with the object of research is KWT Vigur O in Malang - Indonesia. The vegetables grown are Watercress, mustard greens and Pak Choy. Based on the results of the analysis of farming, the highest profit in one harvest for 100m2 of land is Watercress. The majority of farming is a side business that is useful to increase family income. However, there are marketing constraints for KWT Vigur O, so creating a web and building an online network is advisable. Keywords: Urban, Vigur O Women Farmer Group, Organic Vegetables, Farming Business.